Individual vulnerabilities to psychosis after antiepileptic drug administration. Issue 2 (27th August 2020) - Akanuma, Nozomi; Adachi, Naoto; Fenwick, Peter; Ito, Masumi; Okazaki, Mitsutoshi; Hara, Koichiro; Ishii, Ryouhei; Sekimoto, Masanori; Kato, Masaaki; Onuma, Teiichi
Abstract : Background: Psychosis often develops after the administration of antiepileptic drugs (AEDs) in patients with epilepsy. However, the individual vulnerability and clinical condition of such patients have been rarely scrutinised. We investigated the effect of individually consistent (trait-dependent) and inconsistent (state-dependent) characteristics. Methods: The individual characteristics, clinical states and psychotic outcome of patients from eight adult epilepsy clinics were retrospectively reviewed over 6-month periods after a new drug (AED or non-AED) administration between 1981 and 2015. Results: A total of 5018 new drugs (4402 AEDs and 616 non-AEDs) were used in 2015 patients with focal epilepsy. Subsequently, 105 psychotic episodes (81 interictal and 24 postictal) occurred in 89 patients. Twelve patients exhibited multiple episodes after different AED administrations. Trait-dependent characteristics (early onset of epilepsy, known presumed causes of epilepsy, lower intellectual function and a family history of psychosis) were significantly associated with the patients who exhibited psychosis. Absence of family history of epilepsy was also associated with psychosis but not significantly. Subsequent logistic regression analysis with a model incorporating family history of psychosis and epilepsy, and intellectual function was the most appropriate (p=0.000). State-dependent characteristics, including previous psychotic history and epilepsy-related variables (longer duration of epilepsy, AED administration, higher seizure frequency and concomitant use of AEDs) were significantly associated with psychotic episodes. Subsequent analysis found that a model including AED administration and previous psychotic history was the most appropriate (p=0.000). Conclusion: Psychosis occurring after new AED administration was related to the individual vulnerability to psychosis and intractability of epilepsy.